RESPONSE OF SPRING WHEAT ON AGRICULTURAL MEASURES IN THE REGION WITH LOW RAINFALL - L. GaB zewski; . JIaskulska; M. Piekarczyk; D. Jaskulski (Journal of Animal and Plant Sciences, 2019)
The rationale for applying agricultural measures and practices is their confirmed, favourable effect on the growth, development and yield of plants. Each of them, however, interacts with the environmental conditions, particularly soil quality and precipitation distribution during the growing season. The aim of this study was to find the effect of bioregulators applied at different nitrogen fertilization levels and in years with different amounts and distributions of rainfall on some biometric features, yield components and spring wheat yield. A two-factor field experiment was carried out for 4 years differing in the amount and distribution of rainfall during the growing period of spring wheat (2010-2013). Experimental factors were: A – nitrogen fertilization: N1 – 60 kg N·ha-1, N2 – 120 kg N·ha-1; B – bioregulators: B1 - nitrophenols (NPH), B2 – trinexapac-ethyl (TE), B3 – chlorocholine chloride (CCC), B4 – TE + NPH, B5 – CCC + NPH, B6 – no bioregulators (control). The experiment was established in the randomized split-plot design in four replications. In three of the four years of the study there occurred a significant independent effect of nitrogen fertilization and bioregulators application, as well as a combined effect of those factors on spring wheat grain and straw yields. The effect of bioregulators on the number of grains per spike and on the yields was dependent on the year of the study. In the year with a large rainfall deficit from intensive stem elongation, TE application increased the grain yield, whereas CCC application reduced it, but not significantly. These effects were abolished by the combined use of NPH with growth retardants. Nevertheless, in these site conditions the unfavourable effect of CCC on grain yield was increased by additional fertilization with nitrogen. TE and CCC also decreased the yield when rainfall deficit occurred in May, at tillering.
Keywords: chloromequat; nitrophenols; trinexsapac-ethyl; nitrogen dose; precipitation conditions; spring cereal